The Definition and Essence of an Rental Agreement - Ozoda, Khudoynazarova; Oyshabonu, Ravshanova (Journal of Innovation in Education and Social Research, 2024)
This article analyzes the importance of the rent contract in civil law. Also, practical examples are given on this topic.